Corporate Governance dan Kinerja Keuangan - Haniatus Sa’diyah (Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of corporate governance as proxied by the Board of Commissioners, the Board of Independent Commissioners, the Board of Directors and the Sharia Supervisory Board on Financial Performance, through a connecting variable, namely Non Performing Financing (NPF). The sample of this research is using purposive sampling method. The population is 13 Islamic Commercial Banks in Indonesia. The samples obtained were 8 Islamic Commercial Banks. The data is obtained from the quarterly reports of each bank, namely the first quarter of 2017 to the second quarter of 2020. Data analysis and hypothesis testing methods use path analysis using panel data. The results of this study indicate that corporate governance as proxied by the Board of Commissioners, the Independent Commissioner, the Board of Directors and the Sharia Supervisory Board has no effect on financial performance and non-performing financing. This means that higher corporate governance does not affect financial performance or non-performing financing. In this study it was also found that non-performing financing has an effect on financial performance. If non-performing financing decreases, financial performance will increase. In addition, non-performing financing in this study cannot be an intervening variable for corporate governance.